A compact high isolation wideband MIMO antenna for multi-band applications. Issue 14 (22nd September 2022) - Madni, Abdullah; Akram, Muhammad Rizwan; Riaz, Kashif; Rahman, Hamood Ur; Rehman, Mutee Ur; Khan, Wasif Tanveer; Mehmood, Muhammad Qasim
Abstract : Ultra-wideband (UWB) multiple-input-multiple-output (MIMO) antennas promise a wide range of interesting applications in various radio frequency (RF) systems. However, the prime challenges in realizing such systems include achieving a wider bandwidth, significant isolation between the antennas and compactness. This research demonstrates a compact MIMO antenna having a prominent isolation level for portable UWB applications. The proposed antenna comprises two modified rectangular radiating elements with narrow slots in the ground plane, achieving an enhanced bandwidth from 2.1 to 16.9 GHz covering the S, C, X and Ku bands. Meanwhile, two inverted L-shaped stubs are introduced into the ground structure to obtain a higher isolation greater than 16 dB in the entire spectrum. The proposed antenna is of compact size (36 × 38 mm 2 ) and exhibits excellent performance in terms of return loss, mutual coupling, envelope correlation coefficient (ECC), diversity gain (DG) and total active reflection coefficient (TARC).